Survival Outcome of Surgical Resection vs. Radiotherapy in Brain Metastasis From Colorectal Cancer: A Meta-Analysis - Chang, Yu; Wong, Chia-En; Lee, Po-Hsuan; Huang, Chi-Chen; Lee, Jung-Shun (Frontiers in Medicine, 2022)
Background The incidence of brain metastasis from colorectal cancer (CRC) increases along with the greater survival rate for CRC because of the advances in therapeutic modalities. Local treatment strategies for brain metastasis include surgical resection and radiotherapy. Nevertheless, given the incongruent literature, the optimal therapeutic approach remains to be investigated. This study aims to systematically compare the real-world survival outcome of surgical resection and radiotherapy in patients with brain metastasis from CRC. Methods Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines (PROSPERO, ID: CRD42021240200), the Cochrane Library, Embase, and Medline were searched from the inception of the database to August 2021. Meta-analyses were conducted with results pooled using hazard ratios with corresponding 95% CIs to evaluate the overall survival (OS) following local treatment for brain metastasis from CRC. Summary effects were evaluated using a series of random-effect models. Results In this review, 17 retrospective studies comprising 1,438 participants were included. In comparison with radiotherapy, the OS of patients who received brain metastasectomy was generally longer (HR, 0.53; 95% CI, 0.47–0.60). Extracerebral metastases (HR, 1.58; 95% CI, 1.34–1.86) and multiple brain metastases (HR, 1.38; 95% CI, 1.10–1.72) were associated with worse survival outcomes. Conclusions For patients with brain metastasis from CRC, the current real-world evidence demonstrated the survival benefit of aggressive neurosurgical management in suitable patients. Additionally, patients with extracerebral metastases and multiple brain metastases had worse survival outcomes. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=240200.